2016
DOI: 10.1038/srep32140
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Surface Structure Consisting of Contact-active Antibacterial Upper-layer and Antifouling Sub-layer Derived from Gemini Quaternary Ammonium Salt Polyurethanes

Abstract: Contact-active antibacterial surfaces play a vital role in preventing bacterial contamination of artificial surfaces. In the past, numerous researches have been focused on antibacterial surfaces comprising of antifouling upper-layer and antibacterial sub-layer. In this work, we demonstrate a reversed surface structure which integrate antibacterial upper-layer and antifouling sub-layer. These surfaces are prepared by simply casting gemini quaternary ammonium salt waterborne polyurethanes (GWPU) and their blends… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
72
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(73 citation statements)
references
References 46 publications
1
72
0
Order By: Relevance
“…Examples of agents which are mostly used in biocide release antimicrobial coatings are silver ions, triclosan, chlorhexidine, chlorine, tributyltin, nitric oxide, and antibiotics [54]. A commonly studied example of contact active biocidal agent is quaternary ammonium compounds [55, 56]. It is important to note here that some of the biocidal mechanisms of different agents can overlap (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of agents which are mostly used in biocide release antimicrobial coatings are silver ions, triclosan, chlorhexidine, chlorine, tributyltin, nitric oxide, and antibiotics [54]. A commonly studied example of contact active biocidal agent is quaternary ammonium compounds [55, 56]. It is important to note here that some of the biocidal mechanisms of different agents can overlap (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Besides lowering surface tension, gemini surfactants have some exceptional properties which include low cmc value, high surface activity, etc. 11,12 .…”
mentioning
confidence: 99%
“…The Therefore, these results demonstrated that the mechanism of action of these antimicrobial surfaces is by cell-membrane disrupting due to hydrophobic interactions and electrostatic interactions between the negatively charged cell walls and the positively charged copolymers [24][25][26][27] .…”
Section: Evaluation Of the Morphological Changes Of Microbesmentioning
confidence: 99%